Survey of complex influence of physico-chemical and technological parameters on process of milk-egg co-precipitate obtaining - Deinychenko, Grygorii; Zolotukhina, Inna; Skrynnik, Viltoriia; Fedak, Natalia; Tkachyk, Stanislav; Kravchenko, Tamara; Kravchenko, Kateryna; Deinychenko, Liudmyla; Pavliuchenko, Olena; Furmanova, Yuliia (My University, 2020)
The comprehensive effect of the pH medium and the concentration of sugar or sodium chloride on the process of coagulation of egg proteins has been established and analyzed.Визначено та проаналізовано комплексний вплив рН середовища та концентрації цукру або солі на процес коагуляції білків яєць у молочному середовищі.
Keywords: milk and egg concentrate; viscosity of food system; sucrose; sodium chloride; active acidity; молочно-яєчний концентрат; цукор; в’язкість харчової системи; сіль; активна кислотність; кафедра технології ресторанної і аюрведичної продукції